PALEOECOLOGÍA DE OSTRÁCODOS HOLOCENOS DEL ESTUARIO DEL RÍO QUEQUÉN GRANDE (PROVINCIA DE BUENOS AIRES) (Ameghiniana, 2014)
Ostracods from a Holocene outcrop on the northern margin of the Quequén Grande river were studied. Taking into account the ecological characteristics of the ostracod species and the quantitative cornposition of the different associations, a palaeoecological interpretation of the sequence was made. A total of twenty-one taxa were identified; twelve species are illustrated. The base of the studied sequence (7640±90 yr BP) is represented by relatively high energy brackish environments (mesohaline to polyhaline waters). Environments of calm and shallow water with a greater freshwater input and low energy followed; towards the top of the sequence (from 7130±90 yr BP), the ostracod record suggests a marine connection and increasing energy conditions.